3D Parametric Solid Modeling of Cylindrical Indexing Cam based on VB 6.0 and Pro/E - Liu Xiaoqin; Ge Zhenghao; Cao Peng (Jixie chuandong)
On the basis of geometric theory of cylindrical indexing cam,the 3D parametric solid modeling of cylindrical indexing cam is realized based on VB 6. 0 and Pro / E. The friendly interface which can calculate the contour surface data of parametric cylindrical indexing cam is designed through the VB programming language. This interface can be used to calculate the value of the relevant contour surface points through basic parameters input of cam and the choosing of motion law of cam follower,and it will save the file as the format of "ibl". After that,the file is imported into Pro / E 3. 0 to generate curve and then the curves are merged into surface. At last,the normal offset and solid resection operation of theoretical contour surface are carried out,and the cam solid model is obtained after cam blank Boolean subtracting operation.